การสังเคราะห์อนุภาคไอออนิกนาโนพาร์ทิเคิลของเรตินาลสำหรับการนำส่งยาผ่านรูขุมขน - จุฑาภรณ์ อาจนิยม (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Retinal is an alternative precursor of retinoic acid providing a number of benefits such as wound healing, smoothing wrinkles, and reducing fine lines. However, it is a light-sensitive compound and may cause skin irritation in high concentration. Nanoparticles carry and release drug molecules to the target cell effectively. Furthermore, it can minimize the effects of drugs as it releases drug gradually. Calcium citrate nanoparticles are considered to be a non-toxic carrier for drug delivery systems. In this work, retinal was condensed with glycine yielding its Schiff base. Thus, it will enhance the solubility in water and the molecule will be able to encapsulate easily. The product was encapsulated in calcium citrate nanoparticles by coprecipitation method. The size nanoparticles were 685.3 nm as measured with DLS. This method was able to encapsulate retinal-glycine Schiff base nanoparticles and has the potential to further development in cosmeceuticals industry.